Integration Of The Role Of Medical Students And Health Workers In Combating Pulmonary Tuberculosis In North Aceh District - Cut Khairunnisa; Albiner Siagian; Fazidah Aguslina Siregar; Fikarwin Zuska (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Abstract: Pulmonary tuberculosis is a health problem that occurs in almost all countries in the world, including Indonesia. Therefore, in overcoming it, the participation of various elements of society is needed. Purpose: This study aims to create an integrated role for medical students and health workers in the prevention of tuberculosis in the North Aceh Regency. Patients and methods: This study is a qualitative study using a Participatory Action Research design. The number of informants involved consisted of 30 people with TB, 20 medical students, and 4 health workers. Data collection was carried out through in-depth interviews, recording and measurement, and observation of documentation. Results: The results showed that medical assistance by medical students and health workers has increased patient adherence to treatment by 90 percent and the success of TB treatment has also increased by 90 percent. Conclusion: The integration of the role of medical students and health workers can increase the level of adherence and treatment success in pulmonary tuberculosis patients in the North Aceh District.